2023
DOI: 10.1021/acs.iecr.3c01409
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printed Co-continuous Segregated CNT/TPU Composites with Superb Electromagnetic Interference Shielding and Excellent Mechanical Properties

Abstract: Segregated conductive polymer composites (CPCs) have important application prospects in the field of electromagnetic interference (EMI) shielding but suffer from weak mechanical properties that significantly limit their practical applications. In this work, three-dimensional (3D) printing is employed to construct continuous thermoplastic polyurethane (TPU) scaffolds with different interlayer angles of π/5, π/4, π/3, 2π/5, and π/2. Subsequent carbon nanotube (CNT) dip-coating and hot-pressing lead to the succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…(e, f) Tensile stress–strain curves and the tensile modulus of TCP nanocomposites. (g) Ashby charts of the mechanical performance of TCP nanocomposites versus other TPU-based nanocomposites in the previous reports. …”
Section: Resultsmentioning
confidence: 99%
“…(e, f) Tensile stress–strain curves and the tensile modulus of TCP nanocomposites. (g) Ashby charts of the mechanical performance of TCP nanocomposites versus other TPU-based nanocomposites in the previous reports. …”
Section: Resultsmentioning
confidence: 99%
“…Utilizing 3D-printed continuous scaffolds, composites featuring 3D-printed segregated structures are expected to maintain robust mechanical properties. , Figure a illustrates part of typical stress–strain curves of 3D-fillers/PLA with a 30 wt % filler loading, showing a substantial improvement in mechanical performance when compared to the randomly blending samples and the neat PLA matrix (the remaining stress–strain curves are shown in Figure S2. As described in Figure a,b, the tensile strength (19.3 MPa) and the elastic modulus (36.4 MPa) of 3D-L-BN/PLA exhibit a remarkable increase of 99 and 158%, respectively, compared to RM-L-BN/PLA.…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers have shown that it is possible to fabricate 3D-printed sensors using functionalized nanocomposites based on CNTs and TPU [42][43][44]. Niu, Yang et al [45] showed that 3D-printed CNT/TPU composites could offer both EMI-shielding performance and mechanical properties in next generation electronic devices. Wu, Zou et al [46] proves the possibility of 3D printing self-healable strain gauges and humidity sensors using CS/CNT nanocomposites because of their high stretchability and conductivity.…”
Section: Introductionmentioning
confidence: 99%